Kinerja Usahatani Asparagus di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - I MADE DODY DARMAWAN; I WAYAN WIDYANTARA; DEWA GEDE AGUNG (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Asparagus Farm Performance in Pelaga Village, Petang District, Badung Regency. Asparagus farm including a newly developed farming in Bali. The purpose of this study was to determine the allocation of the costs of the farm asparagus, and how the performance of asparagus farming in Pelaga village, Petang District, Badung Regency in terms of BEP analysis and DOL. Costs necessary for the asparagus farming is quite high, Rp. 28.310,00 for a year. Results of the BEP analysis showed that farming asparagus is able to provide benefits to farmers, where the selling price per kg of asparagus in the market (Rp. 28.310.00) greater than the BEP selling price (Rp. 17.625,00) and the price per kg in the market is stable because there was no change to the current price. In terms of quantity, the quantity sold farmers still higher (1.420 kg / year) of the BEP quantity (381 kg / year) with an average land area of ??15 acres. DOL analysis value of 1,37 shows that farm profits will continue to grow in line with increased production in which every 10% increase in production will drive the gain of 13,7%. Asparagus farming is very promising views of BEP analysis and DOL, but in the field there are many farmers experiencing farm constraints, government assistance and mertanadi koperasi particularly needed to assist both in terms of production facilities and technical farming and land development asparagus very well done to make a point higher profits for farmers. Keywords: Asparagus Farm Performance, Analysis of BEP, Analysis of DOL